2017
DOI: 10.21037/jtd.2017.07.11
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation-positive mucinous adenocarcinoma originating in the thymus

Abstract: Thymic carcinoma is a rare, aggressive disease with a low 5-year survival rate. The most common histological neoplastic thymic tumor subtype is squamous cell. We describe an interesting case of a 39-year-old woman who presented with mucinous adenocarcinoma that originated in the thymus and was treated via radical resection and venoplasty of the superior vena cava (SVC). Macroscopically, the resected tumor contained a solid region and multiple cysts with abundant mucin. Microscopic examination showed a papillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…To date, however, only a few English‐language reports have described the genetic abnormalities of thymic adenocarcinoma 5–7 . As such, our case exhibited several novel genetic features, namely, CDKN2A mutations/deletions, an MSI‐H phenotype, and whole‐genome doubling.…”
Section: Discussionmentioning
confidence: 85%
“…To date, however, only a few English‐language reports have described the genetic abnormalities of thymic adenocarcinoma 5–7 . As such, our case exhibited several novel genetic features, namely, CDKN2A mutations/deletions, an MSI‐H phenotype, and whole‐genome doubling.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies identified many genetic aberrations in thymic adenocarcinoma, including a homozygous deletion at the HLA locus and KRAS mutation. [ 6 , 7 , 17 ] But due to the small number of cases, no genetic changes with high incidence were found in thymic adenocarcinomas. KMT2A-MAML2 gene fusion was reported in 4% thymomas (10 of 242), and was considered specific to type B2 and B3 thymomas.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of primary thymic mucinous adenocarcinoma are reported in pathology journals. CT figures and descriptions were found in 11 of 27 cases reported in the English literature (3)(4)(5)(6)(7)(11)(12)(13)(14)(15)(16). We analyzed a total of 12 cases of CT images, including the previous 11 cases and our case.…”
Section: Discussionmentioning
confidence: 99%